You're next - Hurwitz, Gregg Andrew (St. Martin's Press, 2011)
The Boss Man has an unexpected motive in destroying Mike Wingate, who's worked his way up from the bottom to become a successful home contractor in Lost Hills, California. To protect his family and himself, Mike, who was raised in a foster home, summons his only friend from those days, the formidable Shep, who has grown up to be a career criminal of considerable skill.